ANALISIS INVESTASI PERUMAHAN BORNEO NIRWANA RESIDENCE BALIKPAPAN - Irna Hendriyani; Rahmat Rahmat; Reno Pratiwi (INFO-TEKNIK, 2017)
Based on increase of added and population growth that occurred in the city of Balikpapan, therefor the needed and demand for residential will increase. This situation is a business opportunity for developers to build housing complex. Before the construction of the necessary studies on the feasibility of investment projects in terms of economic (financial). Investment method used in the study is the Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PP). The purpose of research is to analyze the feasibility of the Borneo Nirwana Residence housing, that  located in the kelurahan of Karang Joang at street of PDAM. Construction planning was conducted for 10 years with a payback period of 3 years accompanied determination MARR of 9%. The data required to analyze the form of the budget plan will be the cost of land, cost of infrastructure, cost of facilities, cost of office operations, as well as the construction costs of residential buildings. From the analysis, with an invesment cost of Rp.12.863.388.400,00 get the NPV for Rp.2.504.756.281,00 or NPV > 0, and the value of IRR at 9,7 % or IRR > MARR, it can be declared investment is feasible. But in terms of paybak period or PP is not feasible because a value of payback period is above of the desire of developers, that is for 8 years or longer than 5 years of time desired.